Gap formation around Ωe/2 and generation of low-band whistler waves by Landau-resonant electrons in the magnetosphere: Predictions from dispersion theory - Konrad Sauer; Klaus Baumgärtel; Richard Sydora (Earth and Planetary Physics, 2020)
In this paper we show that two significant phenomena of magnetospheric chorus emission can be explained by the participation of beam-like electron structures, created by Landau-resonant interaction with growing oblique whistler waves. The first concerns the widely observed spectral gap near half the electron cyclotron frequency Ωe; the second is related to the observation of very obliquely propagating lower-band waves that cannot be directly generated by temperature anisotropy. Concerning the gap, kinetic dispersion theory reveals that interference of the beam-related cyclotron mode ω~Ωe-kVb with the conventional whistler mode leads to mode splitting and the appearance of a ‘forbidden’ area in the ω-k space. Thereby the beam velocity Vb appears as an essential parameter. It is directly related to the phase velocity of the most unstable whistler wave mode, which is close to VAe/2 for sufficiently hot electrons (VAe is the electron Alfven velocity). To clarify the second point, we show that Landau-resonant beams with Vb < VAe/2, which arise in cold plasmas from unstable upper-band waves, are able to generate lower-band whistler mode waves at very oblique propagation (θ ≥ 60°). Our studies demonstrate the important role of Landau-resonant electrons in nonlinear whistler wave generation in the magnetosphere.